PENERAPAN STRATEGI PEMBELAJARAN AKTIF RODA KEBERUNTUNGAN UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA PADA POKOK BAHASAN KOLOID DI KELAS XI IPA SMA NEGERI 5 PEKANBARU - Karmila, Widya; ', Herdini; ', Erviyenni (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The research aims to improve the learning achievement of student on the subject of Colloid in class XI IPA SMAN 5 Pekanbaru. The research is a kind of experiment research with pretest-posttest design. The samples of this research were the students of class XI IPA 1 as the experiment class and students of class XI IPA 3 as the control class randomly determined after the test of normality and homogeneity test. Experiment class is a class that is applied to active learning strategy of lucky wheel while the control class was not. Data analysis technique used is the t-test. Based on data analysis of data obtained tcount > ttable is 4,78502 > 1,67, means that the use of learning active strategy of lucky whell can improve the learning achievement of students on the subject Colloid in class XI IPA SMAN 5 Pekanbaru with an increase of 22,92%.Keywords :Learning Achievement, Active Learning Strategy of Lucky Wheel, Colloid